Pengembangan Algoritma Manajemen Risiko Proyek Konstruksi - Yetrina, Mutiara (Jurnal Optimasi Sistem Industri, 2018)
The success of a project is uncertain. There is a possibility that the project was successful or failed. Some of the risks that may occur in the project include the arrival of goods or the completion of work late from the time set, design changes due to obstacles in the field, as well as other risks. It is therefore necessary to study the project risks to identify potential problems that may occur and make decisions to reduce risks and increase the likelihood of success of the project. In order for risk management to be performed, the owner must know the steps in evaluating the project and the steps in the implementation of risk management. This study discusses the development of algorithms for project evaluation and risk management. The resulting algorithm is then implemented to the CC-II civil construction project at Indarung VI Project. The results of the implementation show that the project is not running in accordance with the plan. The dominant factors causing delays include BOQ miscalculation by consultants, inadequate and slow decision-making mechanisms, and details of workmanship changes.